2019
DOI: 10.1155/2019/7509690
|View full text |Cite
|
Sign up to set email alerts
|

The Criteria of Underground Rock Structure Failure and Its Implication on Rockburst in Roadway: A Numerical Method

Abstract: Rockburst in roadway happened along with a large-scale destruction of the surrounding rock. To study the failure laws of the surrounding rock in the process of rockburst in roadway, the evolution behaviors of the plastic zone and the criteria of large-scope failure were studied by using FLAC numerical simulation. Meanwhile, the stress response laws of the plastic zone were studied by loading or unloading in a single direction. The results showed that, in the 20 MPa stress environment, large-scale failure zone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Please note that a new combination may generate different result but with a similar implication. According to Guo et al [7], the plastic zone around roadway A is butterfly shaped. According to the directional characteristics of the butterfly-shaped plastic zone, when the direction of the pre-mining stress field rotates around the X axis, the plastic zone around the roadway A would also change correspondingly [28].…”
Section: Modelling Plansmentioning
confidence: 99%
See 1 more Smart Citation
“…Please note that a new combination may generate different result but with a similar implication. According to Guo et al [7], the plastic zone around roadway A is butterfly shaped. According to the directional characteristics of the butterfly-shaped plastic zone, when the direction of the pre-mining stress field rotates around the X axis, the plastic zone around the roadway A would also change correspondingly [28].…”
Section: Modelling Plansmentioning
confidence: 99%
“…Elastic energy and gas energy stored within the intact coal and rock mass are the main sources of energy, and a sudden pressure change induced by the dynamic force source is the main precursor for occurring of the outburst. Guo et al [7] studied the evolution of plastic zone around a roadway using FLAC software and proposed the criteria for underground rock structure failure.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [11,12] analyzed the influence of the nonuniform stress field on the morphology and size of the tunnel plastic zone under the influence of mining and put forward the theory of butterfly-shaped plastic zone. e stability control technology of the surrounding rock with a long bolt is studied and applied in the face of the butterfly failure roadway.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al [5] studied the stress distribution law of rectangular roadways under different span height ratios and lateral pressure coefficients. Guo et al [6] studied the evolution law of plastic zone and large-scale failure criterion of roadway surrounding rock by FLAC numerical simulation method. Wu et al [7,8] found that V-shaped belt failure occurred on both sides of the tunnel through true triaxial experiment and numerical simulation.…”
Section: Introductionmentioning
confidence: 99%